(untitled) (Research, Society and Development, 2025)
The aim of this study was to analyze the nursing team’s knowledge about the use of oxygen during the hospitalization of preterm newborns in the Neonatal Intensive Care Unit. This is an exploratory-descriptive study with a qualitative approach, carried out with ten nursing staff members from the Neonatal Intensive Care Unit of a maternity hospital located in a municipality in the state of Pernambuco. Data was collected through interviews and analyzed using thematic content analysis. Three thematic categories emerged: 1. potential complications related to the use of oxygen therapy; 2. nursing care in oxygen therapy; 3. continuing education and interprofessional communication in the prevention of complications arising from oxygen therapy. The nursing team’s knowledge of oxygen therapy identified retinopathy of prematurity as the main complication associated with the inappropriate use of oxygen. The need for continuing education for the team was highlighted, pointing to communication as a key element for good interprofessional work and quality care for the Preterm Newborn.